Climate Characterization of Strawberry (Fragaria sp.) Growth in the Greenhouse - Putra, Sohnif Nurwicahyo; Sukorini, Henik; Septia, Erfan Dani (Journal of Tropical Crop Science and Technology, 2023)
Strawberries (Fragaria sp.) are a popular fruit and have high commercial value worldwide. Strawberry production continues to increase, but challenges related to temperature and environment affect fruit growth and quality. Temperature is a major factor in strawberry growth. Increased temperature can also affect fruit size, weight, and color, as well as sweetness. This study used a literature search method to analyze the impact of temperature and environment on strawberry growth. To overcome these challenges, the use of greenhouses is one of the appropriate techniques for climate engineering. Greenhouses create suitable temperature conditions and protect plants from adverse climatic conditions and can maintain optimal temperatures for strawberries. Nonetheless, it is necessary to consider the use of shadin g techniques in greenhouses. Relative humidity also plays an important role, and dehumidification techniques, such as dehumidification ventilation, are required to maintain optimal internal conditions.